2020
DOI: 10.1177/1055665620940190
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of Bilateral Cleft Lip and Palate Nasal Deformity

Abstract: Objective: This cross-sectional study utilizes 3-dimensional analysis to assess nasal morphology in patients with bilateral cleft lip and palate (BCLP) compared to controls across the timeline of cleft care. Design: Retrospective comparative cross-sectional study. Setting: Tertiary pediatric academic institution. Patients and Participants: One hundred and twelve patients with BCLP and an equal number of age and sex-matched control participants. Main Outcome Measure(s): Nasolabial angle, nasal length, nasal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…There is agreement that increased NLA is a common feature after BCLP repair compared to controls (Harrison et al, 2020;Meazzini et al, 2010;Seo et al, 2019). It has been suggested that increased columella length from NAM may contribute to this finding (Cutting et al, 1998), and some centers employ columella lengthening surgery as an adjunct to their protocol but this has not been shown to affect nasal tip width or NLA (Harrison et al, 2020). The NAM and primary surgical repair protocol allows the avoidance of secondary columella lengthening surgery, with improved nasolabial appearance through to the completion of nasal growth (Meazzini et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There is agreement that increased NLA is a common feature after BCLP repair compared to controls (Harrison et al, 2020;Meazzini et al, 2010;Seo et al, 2019). It has been suggested that increased columella length from NAM may contribute to this finding (Cutting et al, 1998), and some centers employ columella lengthening surgery as an adjunct to their protocol but this has not been shown to affect nasal tip width or NLA (Harrison et al, 2020). The NAM and primary surgical repair protocol allows the avoidance of secondary columella lengthening surgery, with improved nasolabial appearance through to the completion of nasal growth (Meazzini et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have used 3D photography to characterize the bilateral cleft deformity in a cross-sectional nature, discovering that it is an effective and reproducible tool to assess form (Harrison et al, 2020). There is agreement that increased NLA is a common feature after BCLP repair compared to controls (Harrison et al, 2020;Meazzini et al, 2010;Seo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2012 to 2021, 219 journals have published literature studies in the field of RP research, among which the top 10 most popular journals contributed 1,517 of all 2,590 pieces of literature studies on RP in our study (58.57%) (Table 3). Of these, the top three journals are Plastic and Reconstructive Surgery, Aesthetic Surgery Journal, and JAMA Facial Plastic Surgery, which accounted for about 18 The top 10 cited literature studies about RP…”
Section: The Top 10 Ranked Journals On Publicationmentioning
confidence: 99%
“…Over the years, surgeons have been realizing that it is essential to know how nasolabial features change over time after the primary repair and subsequent surgical and orthodontic interventions, which provides references about residual deformities that may need further revision, and 3D anthropometric technology has been developed rapidly and widely used nowadays in cleft anthropometry (16). Series of longitudinal studies have been implemented according to different interventions (17)(18)(19)(20). Cluster 2 mainly concentrates on functional rhinoplasty.…”
Section: Rankmentioning
confidence: 99%